Outside‐In Systems Pharmacology Combines Innovative Computational Methods With High‐Throughput Whole Vertebrate Studies. (25th April 2018) - Schulthess, Pascal; van Wijk, Rob C.; Krekels, Elke H. J.; Yates, James W. T.; Spaink, Herman P.; van der Graaf, Piet H.
Abstract : To advance the systems approach in pharmacology, experimental models and computational methods need to be integrated from early drug discovery onward. Here, we propose outside‐in model development, a model identification technique to understand and predict the dynamics of a system without requiring prior biological and/or pharmacological knowledge. The advanced data required could be obtained by whole vertebrate, high‐throughput, low‐resource dose‐exposure‐effect experimentation with the zebrafish larva. Combinations of these innovative techniques could improve early drug discovery.